OP0174 POLYDATIN PREVENTS CALCIUM PYROPHOSPHATE CRYSTAL-INDUCED ARTHRITIS IN MICE. (2nd June 2020) - Oliviero, F.; Galuppini, F.; Scanu, A.; Galozzi, P.; Lazzarin, V.; Sfriso, P.; Ravagnan, G.; Ramonda, R.; Spinella, P.; Punzi, L.; Pennelli, G.; Luisetto, R.
Abstract : Background: Acute calcium pyrophosphate (CPP) crystal-induced inflammation is characterized by the massive release of cytokines and pro-inflammatory mediators and, from a clinical point of view, pain and limited joint function. Contrary to the precipitation of urate crystals that can be prevented through the use of hypouricemic drugs, there is no pharmacological therapy that can prevent the formation of pyrophosphate crystals. Polydatin (PD), a natural precursor of resveratrol, is a stilbenoid mainly contained in grape juice and bark of Polygonum Cuspidate. Its antioxidant, anti-inflammatory and immunomodulating properties have been demonstrated in several experimental models. We have recently shown that this compound is able to prevent the inflammatory response to pathogenic crystals in vitro (1). Objectives: The aim of this study was to assess the anti-inflammatory preventing effect of polydatin in the mouse model of acute crystal-induced arthritis. Methods: A suspension of sterile CPP crystals (0.3 mg/20 μL PBS) have been injected intra-articularly (i.a.) into one ankle joint of Balb/c mice under isoflurane anesthesia. Animals were randomized in 5 groups: 1- CPP injection, 2- CPP + PD, 3- CPP + colchicine (control drug), 4- CPP + vehicle (control. N 1), 5- PBS injection (control N. 2). Polydatin and colchicine were administered by gavage (respectively 40 mg/kg and 1mg/kg in 200 μL PBS/EtOH/glucose) at 24, 15 and 1 h before and 1, 6 and 24 h after (prophylactic model) or 1, 6 and 24 h after (therapeutic model) i.a. injection of CPP crystals. Ankle swelling was measured at different time points using a precision caliper. After 48h (peak of the acute phase) mice were euthanized and blood and ankle joints were collected for inflammatory cytokine (IL-1ß and KC) determination and histological analysis, respectively. Results: The mean change in ankle swelling after i.a injection was 0.595±0.434 mm. Prophylactic treatment with PD and colchicine significantly diminished ankle swelling to 0.175±0.115 mm and 0.137±0.100 mm, respectively (Kruskal Wallis p 0.0025; Dunn's post test p < 0.01 CPP vs PD+CPP). The therapeutic administration of PD did not have significant effects on delta swelling (0.468±0.372 mm - PD vs 0.243±0.152 mm - colchicine). In mice treated with CPP crystals, histological analysis revealed areas of edema and increased cell infiltrate in articular and periarticular tissues and the presence of reactive lymphnodes. Tissue necrosis around inflamed tissue has been observed. Treatment with PD importantly reduced cell infiltrate in the prophylactic but not in the therapeutic protocol. Serum IL-1ß and KC levels, which increased significantly (p<0.05) after 48h from i.a injection, diminished in non significant manner after prophylactic and therapeutic treatment. The gene expression study revealed a reduction of IL-1ß and KC mRNA after PD and colchicine treatment in both groups. Conclusion: PD can effectively prevent acute inflammatory response to crystals in the mouse model of CPP arthritis. Oral PD prophylactic treatment showed a similar effect of colchicine in reducing ankle swelling and cell infiltrate. However, only colchicine showed to be effective in the therapeutic protocol. These results raise the possibility that PD might have utility in the prevention of crystal-induced acute attacks in humans. References: [1]Oliviero F, et al. Polydatin and resveratrol inhibit the inflammatory process induced by urate and pyrophosphate crystals in thp-1 cells. Foods 2019 Nov 7;8(11). pii: E560. Disclosure of Interests: Francesca Oliviero: None declared, Francesca Galuppini: None declared, Anna Scanu: None declared, Paola Galozzi: None declared, Vanni Lazzarin: None declared, Paolo Sfriso: None declared, Gianpietro Ravagnan: None declared, Roberta Ramonda Speakers bureau: Novartis, Celgene, Janssen, Pfizer, Abbvie, Lilly, Paolo Spinella: None declared, LEONARDO PUNZI: None declared, Gianmaria Pennelli: None declared, Roberto Luisetto: None declared